322 NEWEST VITAL SIGN: HOW WELL DOES IT SCREEN FOR LOW HEALTH LITERACY?. Issue 1 (1st January 2007) - Rodrigue, C. Z.; Bass, P. F.; Osborn, C. Y.; Wolf, M. S.; Davis, K.; Bocchini, M.; Jain, S.; Davis, T. C.
Abstract : Background: The Newest Vital Sign (NVS) was developed in 2005 to be a rapid screening instrument for low literacy in medical settings. No studies currently compare the NVS with the Rapid Estimate of Adult Literacy in Medicine (REALM), the most commonly used test to screen for literacy in health care settings. Purpose: To compare the performance of the NVS with the REALM and assess the construct validity of the NVS. Methods: A convenience sample of patients at the Primary Care Clinic at LSUHSC was given a structured interview that included demographic information and two literacy assessments, the REALM and the NVS. The REALM is a 66-item word recognition test composed of common health words arranged in order of increasing difficulty. It is highly correlated with standardized reading tests and the Test of Function Health Literacy (0.84). Raw REALM scores can be converted into three grade levels, which represent low, marginal, and adequate literacy levels. The NVS is a nutrition label that tests patients' general literacy and numeracy skills with six questions. For example, patients are asked, "If you usually eat 2, 500 calories in a day, what percentage of your daily value of calories will you be eating if you eat one serving?" A score of 4 to 6 indicates adequate literacy. results: Of the 129 patients tested, age range was 18 to 84 years, 74% were female, 61% African American, and 24% had not graduated from high school. Time to administer the tests was approximately 2 minutes for the REALM and 5 to 7 minutes for the NVS. The internal consistency of the NVS was good (α = 0.81). The correlation between scores on the NVS and scores on the REALM was 0.41 ( p < .001). The Table presents the number and percentage of patients classified as having low/inadequate, marginal, or adequate literacy according to the NVS and REALM. Conclusion: The NVS showed only moderate correlation with the highly validated REALM and did poorly at predicting low literacy as defined by the REALM.